2021
DOI: 10.1016/j.ajo.2020.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Home Monitoring Using a Tablet-Based Visual Field Test (Eyecatcher): An Assessment of Accuracy and Adherence Over 6 Months

Abstract: Purpose To assess accuracy and adherence of visual field (VF) home-monitoring in a pilot sample of glaucoma patients. Design Prospective longitudinal feasibility and reliability study. Methods Twenty adults (median 71 years) with an established diagnosis of glaucoma were issued a tablet-perimeter (Eyecatcher), and were asked to perform one VF home-assessment per eye, per month, for 6 months (12 tests total). Before and after home-monitoring, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 69 publications
3
76
1
1
Order By: Relevance
“…Of note, Jones et al made use of free space viewing when testing a limited 20° region of the central visual field and they also find a high correlation (0.94) between their tablet-based outcomes and repeat HFA 24-2 SITAfast test results. 18 This high concordance is also evident in our Bland-Altman plots ( Figure 7D) and in the Coefficient of Repeatability (CoR) listed in Table 5. The CoR defines the limits that should contain 95% of data on retest and Table 5 shows that the CoR is smaller for the home testing environment derived from 6 tests (4.3 dB) than for the HFA derived from two tests (6.2 dB).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 78%
See 2 more Smart Citations
“…Of note, Jones et al made use of free space viewing when testing a limited 20° region of the central visual field and they also find a high correlation (0.94) between their tablet-based outcomes and repeat HFA 24-2 SITAfast test results. 18 This high concordance is also evident in our Bland-Altman plots ( Figure 7D) and in the Coefficient of Repeatability (CoR) listed in Table 5. The CoR defines the limits that should contain 95% of data on retest and Table 5 shows that the CoR is smaller for the home testing environment derived from 6 tests (4.3 dB) than for the HFA derived from two tests (6.2 dB).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 78%
“…Similar to our study, participants received email reminders on a monthly basis for testing, promoting timely participation although, the timeliness of test returns was not reported by the authors. 18 The high compliance of glaucoma participants achieved in our shorter intervention (87%), appears to flow through to longer term 6monthly trials and suggests that high compliance can be achieved in the long-term in the presence of incentives. This will be the topic of a future paper reporting 12months of clinical follow up of glaucoma patients.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The provision of telemedicine via iPads has been well-received, particularly for its convenience and effectiveness in reducing barriers to assessing specialist care [ 22 ]. Studies also reported good short-term compliance (over 6 months) with home-based visual field monitoring using tablets, and the test results were comparable to measurements in the clinic [ 23 , 24 ]. Validation of VFF may provide an alternative method to facilitate the conduct of telemedicine, by offering means to remotely assess patients with VF complaints.…”
Section: Discussionmentioning
confidence: 57%
“…7 Trials of computer based vision measurements have involved giving participants laptops with known screen parameters. 8,9…”
mentioning
confidence: 99%